Typy konstrukcji drewnianych na terenie Norwegii w Średniowieczu - Barnycz-Gupieniec, Romana (Acta Universitatis Lodziensis. Folia Archaeologica, 1984)
Settlements in Norway were situated mainly in coastal regions, on fertile soils of Oslofiord, and on rugged and irregular Western coast, in adjoining valleys including the region of Trondheim valley. Differentiated landscape acpcunted for differentiation of settlement points and economic activities of the inhabitants. Diversity of structural forms in Norway in the Middle Ages testifies that wooden construction was well developed there already then. Types of timber-work in Norway and in most coastal areas of the Baltic were generally based on the same designs although they differed between them sometimes quite substantially in various details. The pine-tree was providing the most important timber. The oldest Norwegian housing construction, like in the entire Scandinavia, did not make a full use of timber using it mainly as pillars or for roof structures. Walls, on the other hand, were erected from stone and earth or from plaited materials covered with clay. In Norwegian houses timber-framework structures date back to loth century but it may have just as well appeared earlier showing from the very beginning a well-developed form. All the remaining structures, with the exception of framework structures, can be generally classified as pillar structures with this element playing one of more important roles in construction of walls. Approached more widely, pillar-board structures are a common phenomenon of all-European character, while in a more narrow approach – a North-European phenomenon. Pillarboard structures represent this type of construction in which the wall elements are situated vertically. This term is often used in Norway for walle filled with vertically inserted boards. A classical form of such structures are Norwegian churohes, the so-called "stavkirke". Foundations under Norwegian houses differed one from another depending upon the basement soil and wall construction. Sometimes foundations from beams or stones were used alone. Sometimes walls were separated from the wet basement soil by means of dug-in trunk-pillars in corners. Three kinds of floors can be distinguished in Norwegian houses: 1 – earth-clay floors, 2 – stone floors, 3 – wooden floors. Fire-placee were usually placed either in corners or in the centre of a room. Centrally situated fire-places had wooden frames or frames from atone plates. Reconstruction of roof bondings seems to present most problems. This article does not aim at comprehensive analysis of such a rich research area as wooden construction in Norway. The author wanted only to outline briefly the complexity of this problem.